Ensino remoto no período pandêmico: o educador como mediador do aprendizado na educação básica inclusiva um estudo de revisão - BISPO, Regivânia Rabelo (2023)
During the study, two distinct moments will be addressed, the first introductory part refers to the autobiography and the implications inherent to what motivated me to follow the specialization in Pedagogical Practices in language, literacy and literacy and the second part includes an explanation about the challenge of the educator during the pandemic period of Covid-19. The proposal of a direct approach on what motivated the professional to get trained, provided the opportunity to know a little of his history and his challenges to be teaching even today, knowing the numerous challenges made possible by the new coronavirus. Considering this, the search for clarifying a little more about the knowledge of Literacy and Literacy in schools (mainly public ones) and outside them as well, as well as about the theories that we can use to better understand this theme. The literacy process, although a lot of work has been done, continues to be a great challenge in the Brazilian school system. Understanding this, this work arose from the classes of Didactics and Phonology Applied to Literacy, where we observed that there is a close relationship between the way we learn and the way we teach, even though we are not always aware of it. Therefore, this study aims to explain the importance of the literacy and literacy process in the context of basic education, as well as to describe the main challenges faced by educators during the pandemic period of 2020 and 2021. Methodology This is a literature review study, descriptive and argumentative. For the descriptive analysis we used scientific databases such as Sciello, GooglAcademic, and Science direct to search for articles and books that addressed the construction of knowledge during the literacy process. The descriptors chosen for the research were Childhood literacy and literacy, basic education, education in the covid-19 pandemic, education professionals in the pandemic. Development literacy and literacy are different processes, as explained by Emília Ferreiro, each one with its specificities, however, both are indispensable when taking into account the learning of reading and writing. Furthermore, it was possible to verify that the students' social and economic conditions interfere in the literacy and literacy process. Considering this data, it is a fact that social inequality directly influences the access to quality education. With the advent of the new coronavirus pandemic in March 2020, there was the need for the implementation of biosecurity measures such as the use of personal protective equipment (PPE), social distancing, and lockdown to contain the spread of the disease. In addition, the pandemic has made the size of inequality in Brazil even more evident, both in the distribution of economic resources and in the access to education.Final considerations In relation to the current context, it is a time of reconstruction. But it is fundamental that we are encouraged to move forward, and that educators continue to be faithful to their values and vocation, because basic education, the literacy process, is the initial gear for the knowledge and development of a country. Furthermore, as we try to improve our teaching practices, we are being agents of our own pedagogical actions, leaving behind the comfort of traditional practices, based on textbooks or still stuck to obsolete and outdated curricular norms. I know how challenging and complicated it is, especially in public schools. But rethinking about these actions is already a big step towards small future changes.